Aluminum composite film for lithium-manganese battery cap

By adopting a four-layer aluminum composite film and a modified PE layer, combined with a waterproof protective coating, the problems of increased internal resistance, low capacity and shorter storage life of lithium manganese batteries after long-term storage are solved, and the more Good battery performance and longer shelf life.

CN119427854AActive Publication Date: 2025-02-14JIANGMEN HONGLI ENERGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310956312.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2025-02-14
Estimated Expiration
2043-08-01

Smart Images

  • Figure CN119427854A_ABST
    Figure CN119427854A_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum composite film for a lithium-manganese battery cap, and particularly relates to the technical field of lithium-manganese batteries, the aluminum composite film comprises a four-layer structure, the four-layer structure sequentially comprises a protective layer, a middle layer, a composite layer and a heat sealing layer from outside to inside, the protective layer, the middle layer, the composite layer and the heat sealing layer are respectively a first PET layer, an aluminum foil layer, a second PET layer and a modified PE layer, the adjacent structural layers are bonded together through an adhesive, the raw materials of the modified PE layer comprise PE particles, EVA particles and PTFE particles, and the adding percentage of the PE particles is 60-80%, the adding percentage of the EVA particles is 10-20%, and the adding percentage of the PTFE particles is 10-20%. According to the disposable lithium manganese dioxide battery combined by the cap made of the aluminum composite film, the storage life of the battery is long, the self-discharge rate after long-time storage is low, the internal resistance of the battery is not increased along with the increase of the storage time, the electrical property of the battery is better, and the capacity of the battery is higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium manganese battery, and more specifically to an aluminum composite film for lithium manganese battery cap. Background Art

[0002] Aluminum-plastic film is a multilayer film consisting of an outer layer (protective layer) of nylon or PET, an adhesive, an intermediate layer, aluminum foil, an adhesive, and an inner heat-sealing layer. The outermost layer is used to prevent the aluminum foil in the middle from being scratched, and its thickness is generally 15-25μm. The aluminum foil in the middle layer plays a role in preventing oxygen and moisture from invading, and its thickness is generally 35-40μm. The innermost layer is usually polyethylene, and its thickness is generally 40-80μm. Polyethylene separates aluminum and the battery cell, and plays the role of insulation, electrolyte corrosion resistance and packaging. Aluminum-plastic film has extremely high barrier properties and good heat-sealing properties; the material is resistant to electrolyte and strong acid corrosion; and has good ductility, flexibility and mechanical strength.

[0003] Currently, disposable lithium manganese dioxide batteries are all semi-sealed structures, using a cap combination made of old process materials aluminum-plastic film to seal the battery. Long-term storage will lead to problems such as large internal resistance of the battery, low battery capacity and relatively short storage life. Summary of the invention

[0004] In order to overcome the above-mentioned defects of the prior art, the present invention provides an aluminum composite film for a lithium manganese dioxide battery cap. A disposable lithium manganese dioxide battery with a cap assembly made of the aluminum composite film of the present invention has a long storage life, a low self-discharge rate after long-term storage, and the internal resistance of the battery does not increase with the storage time. The battery has better electrical performance and higher capacity.

[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solution: an aluminum composite film for a lithium manganese battery cap, comprising a four-layer structure, wherein the four-layer structure is, from the outside to the inside, a protective layer, an intermediate layer, a composite layer and a heat-sealing layer, wherein the protective layer, the intermediate layer, the composite layer and the heat-sealing layer are respectively a first PET (polyethylene terephthalate) layer, an aluminum foil layer, a second PET layer and a modified PE layer, and adjacent structural layers are bonded together with an adhesive.

[0006] PET has good mechanical properties, high impact strength, good folding resistance, and is resistant to oil, fat, dilute acid, dilute alkali and most solvents. PET can be used for a long time within the temperature range of 55-60°C, and can withstand high temperatures of 65°C and low temperatures of -70°C. It has low gas and water vapor permeability, which means it has excellent gas, water, oil and odor barrier properties. It is non-toxic, odorless, and has good hygiene and safety.

[0007] Aluminum foil is moisture-proof, airtight, light-shielding, abrasion-resistant, and has shielding properties against water vapor, air, ultraviolet rays, and bacteria.

[0008] The raw materials of the modified PE layer include PE (polyethylene) particles, EVA (ethylene-vinyl acetate copolymer) particles and PTFE (polytetrafluoroethylene) particles, and the addition percentages of PE particles, EVA particles and PTFE particles are 60-80%, 10-20% and 10-20% respectively.

[0009] PE is resistant to corrosion by most acids and alkalis, has low water absorption, remains soft at low temperatures, and has high electrical insulation.

[0010] EVA has good chemical stability, aging resistance and ozone resistance.

[0011] PTFE has the advantages of high temperature resistance, low temperature resistance, corrosion resistance, weather resistance and electrical insulation.

[0012] Preferably, the addition percentages of the PE particles, EVA particles and PTFE particles are 60%, 20% and 20% respectively.

[0013] Preferably, the addition percentages of the PE particles, EVA particles and PTFE particles are 70%, 15% and 15% respectively.

[0014] Preferably, the addition percentages of the PE particles, EVA particles and PTFE particles are 80%, 10% and 10% respectively.

[0015] Preferably, the adhesive is a polyurethane adhesive, which has good water resistance, oil resistance, solvent resistance, chemical resistance, ozone resistance, and bacteria resistance, and has good flexibility, resistance to low and ultra-low temperatures, wear resistance, flex resistance, and resistance to bending fatigue.

[0016] Preferably, a protective coating is provided on the outer surface of the protective layer, and the protective coating is obtained by drying a coating.

[0017] Calculated by percentage, the raw materials of the coating include 65% waterborne polyurethane, 12% cationic chloroprene latex, 8% mica powder and 15% flame retardant masterbatch.

[0018] Water-based polyurethane is a waterproof material that is non-toxic and odorless, has good bonding and impermeability, and has strong adhesion. The product has stable chemical properties, large elongation, and good waterproof effect.

[0019] Cationic chloroprene latex is mixed by high molecular polymer, special gelling material and high-quality aggregate according to a special process. It has excellent bonding, crack resistance, frost resistance, seepage resistance, corrosion resistance, wear resistance and aging resistance.

[0020] Mica powder has good elasticity, toughness, insulation, high temperature resistance, acid and alkali resistance, corrosion resistance, and strong adhesion.

[0021] Flame retardant masterbatch is a white granular material made of polyester resin as the main raw material, with various additives added, and then plasticized, mixed and granulated. It has excellent flame retardant properties and processing flowability.

[0022] The present invention also includes a process for preparing an aluminum composite film for a lithium manganese battery cap, and the specific steps are as follows: Step 1: Bond the modified PE layer and the PET layer of the composite layer together by an adhesive, then bond the aluminum foil layer of the middle layer to the outer surface of the PET layer by an adhesive, and then bond the PET layer of the protective layer to the outer surface of the aluminum foil layer by an adhesive.

[0023] Step 2: Finally, a protective coating is applied on the outer surface of the protective layer and then dried to obtain an aluminum composite film for the lithium manganese battery cap.

[0024] Preferably, the preparation method of the intermediate layer is: heating the aluminum metal until it is melted, then injecting the molten aluminum metal into a continuous casting machine, pressing the aluminum metal into an aluminum plate through the action of rollers, and finally sending the aluminum plate into a rolling mill to be rolled into an aluminum foil layer.

[0025] Preferably, the preparation method of the modified PE layer is: S1: PE particles, EVAE particles and PTFEE particles are mixed, and the mixture is fed into an extruder to be heated and melted to become a molten state.

[0026] S2: Using an extruder to extrude the molten mixture into a continuous film.

[0027] S3: The extruded film is rapidly cooled by a cooling roller or a cooling fan to solidify it, and the solidified film is stretched and calendered to prepare a modified PE layer.

[0028] Preferably, the preparation method of the protective coating is: add waterborne polyurethane and cationic chloroprene latex into a stirring kettle, heat it to 50-150°C for stirring, then add mica powder and flame retardant masterbatch, heat it to 200-300°C to obtain the protective coating.

[0029] Technical effects and advantages of the present invention: The aluminum composite film of the present invention is fixed by bonding the first PET layer, the aluminum foil layer, the second PET layer and the modified PE layer at one time by an adhesive, thereby improving the high temperature resistance of the aluminum composite film, giving the aluminum composite film barrier properties to electrolyte, water and gas, and at the same time improving the stiffness of the aluminum composite film, which is beneficial to the processing and forming of the aluminum composite film.

[0030] The protective coating prepared by the present invention has excellent waterproof performance, wear resistance, aging resistance, high temperature resistance, acid and alkali resistance, corrosion resistance, etc., and has strong adhesion, can be stably attached to the outside of the protective layer, and is not easy to fall off. By spraying a layer of protective coating on the outside of the protective layer, the aluminum composite film prepared by the present invention has better performance in blocking electrolyte, water, and gas.

[0031] The disposable lithium manganese dioxide battery with a cap assembly made of the aluminum composite film of the present invention has a long storage life, a low self-discharge rate during long-term storage, and the internal resistance of the battery does not increase with the storage time. The battery has better electrical performance and higher capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a structural diagram of the aluminum composite film of the lithium manganese battery cap of the present invention.

[0033] Figure 2 This is a comparison chart of the weight loss rate of the old process aluminum-plastic film battery and the new process aluminum-plastic film battery during storage at 60°C.

[0034] Figure 3 This is a comparison chart of the internal resistance of the old process aluminum-plastic film battery and the new process aluminum-plastic film battery stored at 60°C.

[0035] The reference numerals in the drawings are: 1 protective layer, 2 intermediate layer, 3 composite layer, 4 heat sealing layer, 5 protective coating layer. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Embodiment 1

[0037] like Figure 1 As shown, the present invention provides an aluminum composite film for a lithium manganese battery cap, comprising a four-layer structure, wherein the four-layer structure is, from the outside to the inside, a protective layer 1, an intermediate layer 2, a composite layer 3 and a heat-sealing layer 4, wherein the protective layer 1, the intermediate layer 2, the composite layer 3 and the heat-sealing layer 4 are respectively a first PET layer, an aluminum foil layer, a second PET layer and a modified PE layer, and adjacent structural layers are bonded together with an adhesive.

[0038] The raw materials of the modified PE layer include PE particles, EVA particles and PTFE particles, and the addition percentages of the PE particles, EVA particles and PTFE particles are 60%, 20% and 20% respectively.

[0039] The adhesive is a polyurethane adhesive.

[0040] The outer surface of the protective layer 1 is provided with a protective coating 5, and the protective coating 5 is made by drying a coating.

[0041] Calculated by percentage, the raw materials of the coating include 65% waterborne polyurethane, 12% cationic chloroprene latex, 8% mica powder and 15% flame retardant masterbatch.

[0042] The present invention also provides a preparation process of the aluminum composite film for lithium manganese battery cap, and the specific steps are as follows: Step 1: Preparation of modified PE layer: S1: PE particles, EVAE particles and PTFEE particles are mixed, and the mixture is fed into an extruder to be heated and melted to become a molten state.

[0043] S2: Using an extruder to extrude the molten mixture into a continuous film.

[0044] S3: The extruded film is rapidly cooled by a cooling roller or a cooling fan to solidify it, and the solidified film is stretched and calendered to prepare a modified PE layer.

[0045] Step 2, preparing the middle layer 2: heating the aluminum metal until it is melted, and then injecting the molten aluminum metal into a continuous casting machine, pressing the aluminum metal into an aluminum plate through the action of rollers, and finally sending the aluminum plate into a rolling mill to be rolled into an aluminum foil layer.

[0046] Step 3: Preparation of protective coating 5: Add waterborne polyurethane and cationic chloroprene latex into a stirring kettle, heat to 50° C. and stir, then add mica powder and flame retardant masterbatch, heat to 200° C. to obtain protective coating 5.

[0047] Step 4: Bond the modified PE layer and the PET layer of the composite layer 3 together with an adhesive, then bond the aluminum foil layer of the intermediate layer 2 to the outer surface of the PET layer with an adhesive, and then bond the PET layer of the protective layer 1 to the outer surface of the aluminum foil layer with an adhesive.

[0048] Step 5: Finally, a protective coating 5 is applied to the outer surface of the protective layer 1 and then dried to obtain an aluminum composite film for the lithium manganese battery cap. Embodiment 2

[0049] like Figure 1 As shown, the present invention provides an aluminum composite film for a lithium manganese battery cap, comprising a four-layer structure, wherein the four-layer structure is, from the outside to the inside, a protective layer 1, an intermediate layer 2, a composite layer 3 and a heat-sealing layer 4, wherein the protective layer 1, the intermediate layer 2, the composite layer 3 and the heat-sealing layer 4 are respectively a first PET layer, an aluminum foil layer, a second PET layer and a modified PE layer, and adjacent structural layers are bonded together with an adhesive.

[0050] The raw materials of the modified PE layer include PE particles, EVA particles and PTFE particles, and the addition percentages of the PE particles, EVA particles and PTFE particles are 70%, 15% and 15% respectively.

[0051] The adhesive is a polyurethane adhesive.

[0052] The outer surface of the protective layer 1 is provided with a protective coating 5, and the protective coating 5 is made by drying a coating.

[0053] Calculated by percentage, the raw materials of the coating include 65% waterborne polyurethane, 12% cationic chloroprene latex, 8% mica powder and 15% flame retardant masterbatch.

[0054] The present invention also provides a preparation process of the aluminum composite film for lithium manganese battery cap, and the specific steps are as follows: Step 1: Preparation of modified PE layer: S1: PE particles, EVAE particles and PTFEE particles are mixed, and the mixture is fed into an extruder to be heated and melted to become a molten state.

[0055] S2: Using an extruder to extrude the molten mixture into a continuous film.

[0056] S3: The extruded film is rapidly cooled by a cooling roller or a cooling fan to solidify it, and the solidified film is stretched and calendered to prepare a modified PE layer.

[0057] Step 2, preparing the middle layer 2: heating the aluminum metal until it is melted, and then injecting the molten aluminum metal into a continuous casting machine, pressing the aluminum metal into an aluminum plate through the action of rollers, and finally sending the aluminum plate into a rolling mill to be rolled into an aluminum foil layer.

[0058] Step 3: Preparation of protective coating 5: Add waterborne polyurethane and cationic chloroprene latex into a stirring kettle, heat to 100° C. for stirring, then add mica powder and flame retardant masterbatch, heat to 250° C. to obtain protective coating 5.

[0059] Step 4: Bond the modified PE layer and the PET layer of the composite layer 3 together with an adhesive, then bond the aluminum foil layer of the intermediate layer 2 to the outer surface of the PET layer with an adhesive, and then bond the PET layer of the protective layer 1 to the outer surface of the aluminum foil layer with an adhesive.

[0060] Step 5: Finally, a protective coating 5 is applied to the outer surface of the protective layer 1 and then dried to obtain an aluminum composite film for the lithium manganese battery cap. Embodiment 3

[0061] like Figure 1As shown, the present invention provides an aluminum composite film for a lithium manganese battery cap, comprising a four-layer structure, wherein the four-layer structure is, from the outside to the inside, a protective layer 1, an intermediate layer 2, a composite layer 3 and a heat-sealing layer 4, wherein the protective layer 1, the intermediate layer 2, the composite layer 3 and the heat-sealing layer 4 are respectively a first PET layer, an aluminum foil layer, a second PET layer and a modified PE layer, and adjacent structural layers are bonded together with an adhesive.

[0062] The raw materials of the modified PE layer include PE particles, EVA particles and PTFE particles, and the addition percentages of the PE particles, EVA particles and PTFE particles are 80%, 10% and 10% respectively.

[0063] The adhesive is a polyurethane adhesive.

[0064] The outer surface of the protective layer 1 is provided with a protective coating 5, and the protective coating 5 is made by drying a coating.

[0065] Calculated by percentage, the raw materials of the coating include 65% waterborne polyurethane, 12% cationic chloroprene latex, 8% mica powder and 15% flame retardant masterbatch.

[0066] The present invention also provides a preparation process of the aluminum composite film for lithium manganese battery cap, and the specific steps are as follows: Step 1: Preparation of modified PE layer: S1: PE particles, EVAE particles and PTFEE particles are mixed, and the mixture is fed into an extruder to be heated and melted to become a molten state.

[0067] S2: Using an extruder to extrude the molten mixture into a continuous film.

[0068] S3: The extruded film is rapidly cooled by a cooling roller or a cooling fan to solidify it, and the solidified film is stretched and calendered to prepare a modified PE layer.

[0069] Step 2, preparing the middle layer 2: heating the aluminum metal until it is melted, and then injecting the molten aluminum metal into a continuous casting machine, pressing the aluminum metal into an aluminum plate through the action of rollers, and finally sending the aluminum plate into a rolling mill to be rolled into an aluminum foil layer.

[0070] Step 3: Preparation of protective coating 5: Add waterborne polyurethane and cationic chloroprene latex into a stirring kettle, heat to 150° C. and stir, then add mica powder and flame retardant masterbatch, heat to 300° C. to obtain protective coating 5.

[0071] Step 4: Bond the modified PE layer and the PET layer of the composite layer 3 together with an adhesive, then bond the aluminum foil layer of the intermediate layer 2 to the outer surface of the PET layer with an adhesive, and then bond the PET layer of the protective layer 1 to the outer surface of the aluminum foil layer with an adhesive.

[0072] Step 5: Finally, a protective coating 5 is applied to the outer surface of the protective layer 1 and then dried to obtain an aluminum composite film for the lithium manganese battery cap.

[0073] Taking CR123A battery as an example, the electrical performance test and battery sealing test of CR123A battery made of aluminum composite film with old process materials and cap made of aluminum composite film with new process materials are as follows: (1) Electrical performance test and battery sealing test of aluminum composite film CR123A battery made of old process materials: a. Storage period test (sample 20 pieces and take the average value after testing); b. Store at a constant temperature of 60℃ for 20 days, which is equivalent to 1 year; discharge capacity is discharged at a constant current of 20mA, and the termination voltage is 2.0V;

[0074]

[0075] (2) Electrical performance test and battery sealing test of aluminum composite film CR123A battery with new process materials: c. Storage period test (sample 20 pieces and take the average value after testing): d. Store at a constant temperature of 60℃ for 20 days, which is equivalent to 1 year; discharge capacity is discharged at a constant current of 20mA, and the termination voltage is 2.0V;

[0076]

[0077] like Figure 1 This is a comparison chart of the weight loss rate of the old process aluminum-plastic film battery and the new process aluminum-plastic film battery at 60°C; Figure 2 This is a comparison chart of the internal resistance of the old process aluminum-plastic film battery and the new process aluminum-plastic film battery stored at 60°C.

[0078] The storage period of disposable lithium manganese dioxide batteries with aluminum composite film capping assemblies made of old process materials is generally 3-5 years. The storage period of the battery with aluminum composite film capping assemblies made of the new process materials of the present invention can reach 8-10 years. The internal resistance of the battery made of the new process aluminum composite film does not increase with the storage time, and is always maintained at about 300 milliohms, so that the battery has better electrical performance and higher capacity.

[0079] Finally: The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An aluminum composite film for lithium manganese battery cap, characterized in that: The invention comprises a four-layer structure, which comprises, from the outside to the inside, a protective layer (1), an intermediate layer (2), a composite layer (3) and a heat-sealing layer (4), wherein the protective layer (1), the intermediate layer (2), the composite layer (3) and the heat-sealing layer (4) are respectively a first PET layer, an aluminum foil layer, a second PET layer and a modified PE layer, and adjacent structural layers are bonded together by an adhesive; the raw materials of the modified PE layer comprise PE particles, EVA particles and PTFE particles, and the addition percentages of the PE particles, the EVA particles and the PTFE particles are respectively 60-80%, 10-20% and 10-20%.

2. The aluminum composite film for lithium manganese battery cap according to claim 1, characterized in that: The addition percentages of the PE particles, EVA particles and PTFE particles are 60%, 20% and 20% respectively.

3. The aluminum composite film for lithium manganese battery cap according to claim 1, characterized in that: The addition percentages of the PE particles, EVA particles and PTFE particles are 70%, 15% and 15% respectively.

4. The aluminum composite film for lithium manganese battery cap according to claim 1, characterized in that: The addition percentages of the PE particles, EVA particles and PTFE particles are 80%, 10% and 10% respectively.

5. The aluminum composite film for lithium manganese battery cap according to claim 1, characterized in that: The adhesive is a polyurethane adhesive.

6. The aluminum composite film for lithium manganese battery cap according to claim 1, characterized in that: The outer surface of the protective layer (1) is provided with a protective coating (5), and the protective coating (5) is obtained by drying a coating; in terms of percentage, the raw materials of the coating include 65% waterborne polyurethane, 12% cationic chloroprene latex, 8% mica powder, and 15% flame retardant masterbatch.

7. A process for preparing the aluminum composite film for lithium manganese battery cap according to any one of claims 1 to 6, characterized in that: The specific steps are as follows: Step 1: bonding the modified PE layer and the PET layer of the composite layer (3) together by means of an adhesive, then bonding the aluminum foil layer of the intermediate layer (2) to the outer surface of the PET layer by means of an adhesive, and then bonding the PET layer of the protective layer (1) to the outer surface of the aluminum foil layer by means of an adhesive; Step 2: Finally, a protective coating (5) is applied to the outer surface of the protective layer (1) and then dried to obtain an aluminum composite film for the lithium manganese battery cap.

8. The process for preparing the aluminum composite film for lithium manganese battery cap according to claim 7, characterized in that: The preparation method of the intermediate layer (2) is as follows: heating aluminum metal until it is melted, then injecting the molten aluminum metal into a continuous casting machine, pressing the aluminum metal into an aluminum plate through the action of rollers, and finally sending the aluminum plate into a rolling mill to be rolled into an aluminum foil layer.

9. The process for preparing the aluminum composite film for lithium manganese battery cap according to claim 7, characterized in that: The preparation method of the modified PE layer is: S1: Mix PE particles, EVAE particles and PTFEE particles, feed the mixture into an extruder, and heat and melt it into a molten state; S2: using an extruder to extrude the molten mixture into a continuous film; S3: The extruded film is rapidly cooled by a cooling roller or a cooling fan to solidify it, and the solidified film is stretched and calendered to prepare a modified PE layer.

10. The process for preparing the aluminum composite film for lithium manganese battery cap according to claim 7, characterized in that: The preparation method of the protective coating (5) is as follows: adding waterborne polyurethane and cationic chloroprene latex into a stirring kettle, heating to 50-150°C for stirring, then adding mica powder and flame retardant masterbatch, heating to 200-300°C, and preparing the protective coating (5).

Citation Information

Patent Citations

  • High-barrier type acid-resisting and stress-resisting aluminum plastic film for lithium battery

    CN105034489A

  • Back plate film of solar battery

    CN206510551U

  • Nonaqueous secondary battery

    JP2000251857A

  • Manufacturing method of lithium containing metal oxide and lithium secondary battery using same

    JP2004164988A

  • Packing material for lithium ion battery

    JP2011108450A